2012
DOI: 10.1002/bio.1371
|View full text |Cite
|
Sign up to set email alerts
|

Dy3+and Mn2+ emission in fluoride‐ and chloride‐based Na3(SO4)X (X = F or Cl) phosphors

Abstract: In the present study, Na3 (SO4)X (X = F or Cl) halosulphate phosphors have been synthesized by the solid-state diffusion method. The phase formation of the compounds Na3 (SO4)F and Na3 (SO4)Cl were confirmed by X-ray powder diffraction (XRD) measurement. Photoluminescence (PL) excitation spectrum measurement of Na3 (SO4)F:Ce3+ and Na3 (SO4)Cl:Ce3+ shows this phosphor can be efficiently excited by near-ultraviolet (UV) light and presents a dominant luminescence band centred at 341 nm for Ce3+, which is responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…It has been suggested that the dopants do not change the nature of traps already existing in the host matrix, giving only different luminescence efficiencies . We have developed some phosphors such as Na 3 (SO 4 )F, Na 3 (SO 4 )Cl , NaMgSO 4 F , Na 6 (SO 4 ) 2 FCl , K 3 Ca 2 (SO 4 ) 4 F , KZnSO 4 Cl , and KMgSO 4 Cl by wet chemical and solid‐state synthesis methods. Rare‐earth ions‐doped mixed alkali/alkaline sulfate phosphors have well desired characteristics such as a high temperature glow peak, linear response with ionizing radiation exposure, negligible fading and an easy method of preparation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the dopants do not change the nature of traps already existing in the host matrix, giving only different luminescence efficiencies . We have developed some phosphors such as Na 3 (SO 4 )F, Na 3 (SO 4 )Cl , NaMgSO 4 F , Na 6 (SO 4 ) 2 FCl , K 3 Ca 2 (SO 4 ) 4 F , KZnSO 4 Cl , and KMgSO 4 Cl by wet chemical and solid‐state synthesis methods. Rare‐earth ions‐doped mixed alkali/alkaline sulfate phosphors have well desired characteristics such as a high temperature glow peak, linear response with ionizing radiation exposure, negligible fading and an easy method of preparation.…”
Section: Introductionmentioning
confidence: 99%